2016
DOI: 10.17096/jiufd.96734
|View full text |Cite
|
Sign up to set email alerts
|

Reciproc Versus Twisted File for Root Canal Filling Removal: Assessment of Apically Extruded Debris

Abstract: Purpose:The aim of this study was to evaluate the amount of apically extruded debris during endodontic retreatment with different file systems. Materials and Methods:Sixty extracted human mandibular premolar teeth were used in this study. Root canals of the teeth were instrumented and filled before being randomly assigned to three groups. Guttapercha was removed using the Reciproc system, the Twisted File system (TF), and Hedström-files (H-file). Apically extruded debris was collected and dried in pre-weighed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 41 publications
(79 reference statements)
0
7
1
Order By: Relevance
“…Numerous studies show that Reciproc was more resistant compared to other continuous and alternating systems. The difference, grouped as per mean time of fracture, was longer for the Reciproc system compared to WaveOne by 45.6 seconds (14) . Other studies also found that Reciproc had better resistance to flexural fatigue because of its cross section, to the angles and speed of reciprocation (35) .…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Numerous studies show that Reciproc was more resistant compared to other continuous and alternating systems. The difference, grouped as per mean time of fracture, was longer for the Reciproc system compared to WaveOne by 45.6 seconds (14) . Other studies also found that Reciproc had better resistance to flexural fatigue because of its cross section, to the angles and speed of reciprocation (35) .…”
Section: Discussionmentioning
confidence: 94%
“…Several studies support the resistance of Reciproc (14,17,(42)(43)45) and agree it has greater cyclic fatigue , . Contrary to the results obtained by Ozyurek et al (14) , they compared the resistance to cyclic fatigue of WaveOne, WaveOne Gold and Reciproc, and concluded that WaveOne Gold showed greater resistance to cyclic fatigue. In a study conducted by Topcuoglu et al (54) Reciproc presented greater resistance to cyclic fatigue than WaveOne in apical curvatures, but not in the cervical third.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations